The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1108/lodj-10-2013-0135
|View full text |Cite
|
Sign up to set email alerts
|

Seeking and measuring the essential behaviors of servant leadership

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 67 publications
(126 reference statements)
0
70
1
2
Order By: Relevance
“…Winston and Fields (2015) assessed and measured the important behavior of servant leadership; the results indicate that servant leadership has a relationship with performance. Chan and Wai-ming (2014) examined the impact of servant leadership on trust, attitudes and employees; the results show that servant leadership has a positive impact on employee performance.…”
Section: Discussion Relationship Between Servant Leadership and Emplmentioning
confidence: 99%
See 1 more Smart Citation
“…Winston and Fields (2015) assessed and measured the important behavior of servant leadership; the results indicate that servant leadership has a relationship with performance. Chan and Wai-ming (2014) examined the impact of servant leadership on trust, attitudes and employees; the results show that servant leadership has a positive impact on employee performance.…”
Section: Discussion Relationship Between Servant Leadership and Emplmentioning
confidence: 99%
“…Winston and Fields (2015), Chan and Wai-ming (2014), Retmono (2013), Krisna and Kripa (2012), and Melchar and Bosco (2010), suggest that servant leadership can have an impact on performance. However, Rocco (2016) has found that servant leadership does not necessarily result in an increase in employee performance.…”
mentioning
confidence: 99%
“…Previous studies (e.g., Reid et al, ; Van Winkle et al, ) have shown this measure to exhibit good internal reliability. Winston and Fields () report evidence of convergent validity with Liden et al’s () servant leadership measure, as well as discriminant validity from measures of transformational leadership and leadership effectiveness. In this study, Cronbach's alpha was .92.…”
Section: Literature and Conceptual Modelmentioning
confidence: 99%
“…Servant leadership has received growing interest from leadership practitioners and researchers (Parris & Peachey, ), including nonprofit scholars (Palumbo, ; Ronquillo et al, ). Greenleaf () states that servant leadership starts with the leader's desire to serve and focuses on the follower through “facilitating follower performance and development” (Winston & Fields, , p. 414). Similar suggestions have been made about effective nonprofit executive leaders who are focused on their board members' needs, who facilitate their board members' performance, are responsive to their stakeholders, and who lead beyond the boundaries of the organization (Herman, ).…”
Section: Literature and Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation